Peran Orang Tua Dalam Membentuk Karakter Anak Usia Dini Di Tengah Era Digital Dan Globalisasi - Ningtya Ayu, Sara; Sit, Masganti; Siregar, Nur Hairani; Anisa Hasibuan, Yuli (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to analyze the role of parents in shaping early childhood character amid the rapid development of the digital era and globalization. Using a descriptive qualitative method, the research involved 10 parents and 3–6 teachers from Raudhatul Athfal (RA) Al-Fajar in Medan as participants. Data were collected through semi-structured interviews, observations, and literature review. The findings show that parental involvement—particularly in monitoring children’s digital media use, providing behavioral modeling, and maintaining open communication—significantly contributes to the development of moral, social, and emotional character in children aged 4–6 years. Parents who consistently supervise gadget use and instill values such as empathy, discipline, and responsibility demonstrated greater effectiveness in strengthening children’s character. However, limited digital literacy and time constraints remain major challenges for parents. This study highlights the need for collaboration between families, schools, and communities to create a supportive environment for character education. The results provide practical implications for strengthening family-based character development strategies in navigating digital challenges and global cultural influences